If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2*x)/3-(2/3) = (-7*x)/2+(4*x)/3 // - (-7*x)/2+(4*x)/3
(2*x)/3-((-7*x)/2)-((4*x)/3)-(2/3) = 0
(2*x)/3+(7/2)*x+(-4/3)*x-2/3 = 0
17/6*x-2/3 = 0 // + 2/3
17/6*x = 2/3 // : 17/6
x = 2/3/17/6
x = 4/17
x = 4/17
| 15.96+2s=T | | y=-3x-69 | | (x+10)/2=7(x-1) | | T=2s+25.96 | | x+2y=-18 | | .5q=315 | | -2=-2(3x-5) | | 1.9y-1.6y= | | -2x-3y=1 | | 5q=315 | | y^11+6=-7 | | 2+2x=4x-8 | | -4x-12y=36 | | y^3+5=-7 | | -16t^2-11t+150=0 | | 3x-12y=27 | | -5(-3q+11)+4(-1-5q)= | | -8p-2p=3+1-6p-5p | | 9n^2-3n=2 | | 3y+3x=36 | | 64n^2=49 | | 5n^2=20n | | 5x^2-1=3 | | 6n^3-22n^2=3n-11 | | -8x+7x=9 | | 2x-3y=-18 | | 27s^7/49s*21s^6/243s | | T=5s+18.38 | | 34x=17x+9 | | 1x+1x+7=2x+3 | | 5x^2+2x-7/2x^2-7x-4/25x^2+55x+28/2x^2+3x+1 | | 5ab-a+3ab-ab= |